NEUROSAINS DALAM PEMBELAJARAN DI PENDIDIKAN DASAR: TINJAUAN LITERATUR TENTANG STRATEGI MENINGKATKAN ATENSI DAN RETENSI SISWA - Hendrizal; Firsty Sofila; Febrio Rozalmi Putra; Roza Naulia Rosdianti; Yustina; Yusparni Yetti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving student attention and retention is an important aspect of learning in primary education. This study aims to examine neuroscience-based learning strategies that can improve student attention and memory. The method used is a literature review, examining various relevant journals, books, and recent scientific articles. The findings indicate that approaches such as multisensory learning, the use of mnemonic techniques, spaced repetition, and the integration of physical activities in learning are effective in supporting students' cognitive functions. These strategies align with theories of brain neuroplasticity, working memory theory, and the role of emotions in learning. Additionally, factors such as sleep quality and nutrition also play a significant role in supporting students' attention and retention abilities. These findings suggest that learning designed based on neuroscience principles can create a more effective and responsive learning environment tailored to students' needs.